Sprzeczność i inne typy dewiacji językowych w polu komentarzy metatekstowych - Żabowska, Magdalena (Linguistica Copernicana, 2023)
The subject of the paper is a description of the connectivity of metatextual comments, the aim is to show deviant combinations of expressions at this metatext level, which are a consequence of general rules for the utterance, i.e., currently used sentences. I describe the general properties of metatextual commentaries from which the requirements and limitations of their connectivity arise (§ 2). Based on the analysis of connectivity of metatextual commentaries, I present an index of textual relations realized with them (§ 3). Then I present deviant combinations of metatextual comments with expressions filling the items opened by them. As a result of this procedure, I distinguish three types of linguistic deviations arising at this level of the metatext, i.e., pragmatic, illocutionary and utterance contradiction, and their subtypes (§ 4).